An examination of the pre-competition and post-competition state anxiety levels of Russian women`s national volleyball team athletes - Sekeroglu, M. Ö. (Journal of Education and Training Studies, 2019)
This study of 14 Russian women`s national volleyball team athletes aimed to determine their pre-competition and post-competition state anxiety levels according to some variables. This descriptive study used the Competition State Anxiety Inventory-2 (CSAI-2) developed by Martens, Burton, Vealey, Bump and Smith (1990). This inventory has 9 items in 3 sub-factors: cognitive anxiety, somatic anxiety and self-confidence.